Lived experience of young females raised by social fathers : a case of Driekop Community, Limpopo Province, South Africa - Rantho, Katlego Magdeline (My University, 2024)
The number of children growing up in stepfamilies is rising globally. This rise is accelerated due to parental remarriage following divorce, death or immigration. Undeniably, children growing in these newly formed stepfamilies remain susceptible to enormous challenges at the hands of their stepparents, most particularly young females. Amongst other challenges, these children may experience psychological, emotional, and academic challenges. The aim of this study was to describe the lived experiences of young females raised by social fathers in the Driekop community in the South African Limpopo province. The study adopted a qualitative research approach and utilised a phenomenological research design to obtain first-hand information from the research participants. The research targeted young black females raised by social fathers in Driekop community in Limpopo province. Seven participants were sampled using the purposive sampling technique, which falls under the non-probability sampling methods. Data was collected through face-to-face interviews, and the data was analysed using an inductive thematic analysis method. The study found that young females raised by social fathers suffer from psychological challenges, such as feelings of worthlessness, loneliness, a lack of sense of belonging, fear of abuse, and being unable to speak about their challenges. It was also established that these young females are discriminated against, and that they lack their mothers’ support when they raise the challenges that they face due to the presence of their social fathers. To cope with these challenges, the young females resort to seeking support from their significant others, pray, and/or use substances, such as alcohol to numb the pain. This study recommends educational campaigns that could assist both young females and social fathers in adjusting to the new living circumstances. The study also recommends awareness campaigns to educate and encourage young females to report any form of abuse by their social fathers
Thesis (M. A. (Psychology)) -- University of Limpopo, 2024
Keywords: Challenges; Coping Mechanism; Lived Experience; Psychological; Social Fathers; Young Female; Fathers -- South Africa -- Limpopo Province; Girls; Adjustment (Psychology); Families